2021
DOI: 10.1371/journal.pntd.0009904
|View full text |Cite
|
Sign up to set email alerts
|

Safely resuming neglected tropical disease control activities during COVID-19: Perspectives from Nigeria and Guinea

Abstract: Since its early spread in early 2020, the disease caused by the novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Coronavirus Disease 2019 (COVID-19) has caused mass disruptions to health services. These have included interruptions to programs that aimed to prevent, control, and eliminate neglected tropical diseases (NTDs). In March 2020, the World Health Organization (WHO) released interim guidelines recommending the temporary cessation of mass drug administration (MDA), community-based surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…It is possible that relationships between stakeholders dwindled during this period due to the focus of the health system on the pandemic. However, the effect of the pandemic on NTD activities was limited within the country and the streamlining of Covid-19 prevention activities into the NTD control activities ensured that NTD stakeholders were active during the research period [ 35 ]. Second, stakeholders interviewed gave a self-report of relationships which may be subject to over or under-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that relationships between stakeholders dwindled during this period due to the focus of the health system on the pandemic. However, the effect of the pandemic on NTD activities was limited within the country and the streamlining of Covid-19 prevention activities into the NTD control activities ensured that NTD stakeholders were active during the research period [ 35 ]. Second, stakeholders interviewed gave a self-report of relationships which may be subject to over or under-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is acknowledged that there will be substantial challenges to implementing the mitigation strategies that we have modelled, and many studies aiming to evaluate the challenges of programmatic restarts have emphasised the increased costs associated with effectively delivering community-based NTD activities in the context of COVID-19. 10 , 13 , 14 , 51 , 52 , 53 , 54 Reasons given for increased costs include personal protective equipment, the need for enhanced training, time taken for sensitisation to overcome hesitancy or refusals due to the misinformation about the pandemic, and increased costs associated with delivering mass drug administration door to door (rather than community delivery at a central distribution point, or schools-based delivery for soil-transmitted helminths and schistosomiasis).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 However, substantial challenges and service gaps have been reported, including missed rounds of mass drug administration and vector control (eg, indoor residual spraying of insecticide) in 2020; hesitancy or refusal of communities to participate; reassignment of NTD programme personnel to support COVID-19 interventions; delays in active case finding and presentation of cases to health facilities (passive case detection); delays in manufacture and supply of NTD medicines; and discontinuation of monitoring and evaluation activities, including population-based surveys. 10 , 11 , 12 , 13 , 14 The 2021 national pulse survey, carried out by WHO on continuity of essential health services during the COVID-19 pandemic, found that the proportion of countries reporting severe disruptions to NTD activities was the highest of all health services, with mass drug administration reported to be both the most frequently and most severely affected of all NTD services. 12 This finding raises serious concerns that the indirect effect of the COVID-19 pandemic could lead to substantial losses to many of the achievements of recent years (eg, the ten-fold reductions in incidence of human African trypanosomiasis since 2013 and the five-fold reductions in incidence of visceral leishmaniasis since 2011, both diseases that require case-finding and disease management), and threaten progress towards the 2021–30 targets proposed by the second WHO roadmap on NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, es vital tener una difusión masiva de información, riesgos y prevención de las ETDs, adaptado a todos los niveles educativos y sociales, tal como se hizo con la pandemia COVID-19, para que en un futuro exista una mayor participación de la población y una menor incidencia de infecciones. Se deben unir fuerzas políticas y privadas para impulsar el desarrollo de nuevos tratamientos y métodos diagnósticos, además de promover un aumento del presupuesto para los programas (Ehrenberg et al 2020, Mckay et al 2021.…”
Section: Estrategias Para La Prevención De Las Etds Durante Covid-19unclassified